2007
DOI: 10.1021/jf070121j
|View full text |Cite
|
Sign up to set email alerts
|

A New Process To Develop a Cocoa Powder with Higher Flavonoid Monomer Content and Enhanced Bioavailability in Healthy Humans

Abstract: Cocoa is a food rich in polyphenols, mainly the flavonoid procyanidins and flavan-3-ols. The improvement of the cardiovascular function in humans upon cocoa consumption has been specifically linked to the presence of flavan-3-ol derived metabolites in plasma, especially epicatechin glucuronide. In this context, a flavonoid-enriched cocoa-derived product could potentially exert stronger health benefits. The aim of the present study was to obtain a cocoa powder with a higher flavonoid content (mainly enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
158
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(179 citation statements)
references
References 27 publications
12
158
1
8
Order By: Relevance
“…Phenolic compounds are one of the most important groups of secondary metabolites directly related to the sensory characteristics (color and bitter taste) and many beneficial health effects of raw cocoa beans and their derived products [1][2][3]. The most abundant class of polyphenols identified in cocoa beans has been flavonoids [4]. Among these compounds, monomeric flavan-3-ols (37 %), such as (−)-epicatechin and (+)-catechin, as well as procyanidins (58 %) with various degrees of polymerization are the most important ones [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic compounds are one of the most important groups of secondary metabolites directly related to the sensory characteristics (color and bitter taste) and many beneficial health effects of raw cocoa beans and their derived products [1][2][3]. The most abundant class of polyphenols identified in cocoa beans has been flavonoids [4]. Among these compounds, monomeric flavan-3-ols (37 %), such as (−)-epicatechin and (+)-catechin, as well as procyanidins (58 %) with various degrees of polymerization are the most important ones [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds confer bioactive properties on the cocoa beans and cocoa-derived products, such as antitumorigenic, antimutagenic, anti-inflammatory, antiadhesive, and antioxidant effects. In this sense, it has been reported that consumption of flavanol-rich cocoa products have been found to decrease the risk of cancer and cardiovascular diseases, improve blood lipid profile and 1 3 endothelial function, inhibiting platelet aggregation, and reduce inflammatory response [4,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, los valores obtenidos en los granos sin fermentar (F0) se encuentran por debajo de aquellos reportados en estudios similares. Así por ejemplo, Tomas-Barberán et al [29] hallaron un contenido polifenólico total de 81,4mgEAG/gMS en un clon amazónico colombiano seco y sin fermentar. Kim y Keeney [30] encontraron contenidos de PT en granos de cacao forastero no fermentado entre 120 y 180mgEAG/gMS.…”
Section: Contenido De Polifenoles Totales (Pt)unclassified
“…Se observa que el valor predicho para el nivel 0 de fermentación se aleja considerablemente del contenido de PT establecido en el presente estudio, acercándose a su vez a lo reportado por otros autores [29][30][31][32]. Aunque la expresión propuesta en este trabajo fue ajustada con valores propios del clon de cacao CCN-51, ella también permite predecir la evolución del contenido de PT de variedades Forastero y Amazónico con un error relativo promedio del 20%, aproximadamente (Tabla 3).…”
Section: Etapa Final (F6 Y F8)unclassified